Concept of Resilience in Islamic Perspective - Rochman, Fauzi; Nugroho, Wahyu Budi; Albany, Sulistiono Shalladdin; Ikhsani, Hanif; Sukiman, Sukiman; Hakim, Ikhsan; Rachman, Suryahadi Yulia (Universitas Muhammadiyah Yogyakarta, 2024)
The examination of resilience within the framework of positive psychology is constrained in its ability to elucidate the experiences of individuals residing in a social and religious milieu. The literature evaluation has not extensively examined resilience from an Islamic perspective. The objective of this study is to examine the concept of resilience from an Islamic standpoint by conducting a comprehensive analysis of relevant material published between 2010 and 2022, both at the national and international levels. The research methodology employed is qualitative, utilizing descriptive analysis. The approach adopted for this study is a literature review or library study. The data is sourced from the Google Scholar database by utilizing specific keywords and exclusion criteria. The process of analyzing data was conducted through the use of content analysis. The research yielded a total of 30 articles in the initial stage. After a screening process, 16 articles that did not fulfill the criteria were eliminated, leaving 4 articles for the subsequent content analysis stage. Content analysis reveals that resilience, from an Islamic standpoint, refers to an individual's capacity and fortitude to endure and adapt in the face of adversity, enabling them to overcome the challenges and maintain patience and submission to Allah. Resilience, from an Islamic standpoint, encompasses various elements such as adaptability, the capacity to acquire knowledge from experiences, a positive outlook and belief in one's own abilities, the ability to restrain cravings, empathy, and being trustworthy and responsible.